2020
DOI: 10.21203/rs.2.23386/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cervical and oral human papillomavirus infection in women living with human immunodeficiency virus (HIV) and matched HIV-negative controls in Brazil

Abstract: Background: Despite the demonstrated role of human Papillomavirus (HPV) in the etiology of cervical cancer and the strong evidence suggesting the importance of HPV in the development of oropharyngeal cancer, several aspects of the interrelationship between HPV infection in both body sites remain unknown, specifically in female human immunodeficiency virus (HIV)-positive (HIV+) patients. We aimed to assess the prevalence, distribution, and concordance of cervical and oral HPV in HIV+ women and matched HIV-negat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This review sought to identify HPV genotypes by cervical disease grade in WHIV in LAC but identified a lack of published data from LAC, despite having some of the highest rates of HIV, HPV and cervical cancer. There are 2 recent studies from Brazil that demonstrated that WHIV are more likely to have an oncogenic HPV infection, that HPV genotypes varied in the cervix versus the oropharynx, and that WHIV had higher prevalence of cytological abnormalities 24,25 . Suehiro et al, 24 reported that among 231 WHIV, 6 women (2.6%) had HSIL with a HR-HPV infection but did not have specific genotyping performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review sought to identify HPV genotypes by cervical disease grade in WHIV in LAC but identified a lack of published data from LAC, despite having some of the highest rates of HIV, HPV and cervical cancer. There are 2 recent studies from Brazil that demonstrated that WHIV are more likely to have an oncogenic HPV infection, that HPV genotypes varied in the cervix versus the oropharynx, and that WHIV had higher prevalence of cytological abnormalities 24,25 . Suehiro et al, 24 reported that among 231 WHIV, 6 women (2.6%) had HSIL with a HR-HPV infection but did not have specific genotyping performed.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 recent studies from Brazil that demonstrated that WHIV are more likely to have an oncogenic HPV infection, that HPV genotypes varied in the cervix versus the oropharynx, and that WHIV had higher prevalence of cytological abnormalities 24,25 . Suehiro et al, 24 reported that among 231 WHIV, 6 women (2.6%) had HSIL with a HR-HPV infection but did not have specific genotyping performed. Of all new cases of cervical cancer diagnosed 86% will occur in Africa, LAC, and portions of Asia, yet most data guiding HPV-based cervical screening comes from Africa or Europe/North America 16 .…”
Section: Discussionmentioning
confidence: 99%